Teacher Performance in Literacy Learning at Elementary School - Sani Aryanto; Sri Wulandari; Decenni Amelia; Ade Putri Puspitasari (Green Publisher, 2026)
Teacher performance is widely regarded as one of the strongest school based determinants of literacy learning outcomes among elementary school students, yet evidence on which dimensions matter most remains scattered across disciplines. This study used a systematic literature review guided by the PRISMA 2020 protocol to synthesize 50 empirical and review articles from reputable Scopus indexed international journals (SJR quartile Q1 or Q2, SJR ≥ 0.025, active/non discontinued) published between 2015 and 2026. Following a structured search of Scopus, Web of Science, ScienceDirect, Wiley, SAGE, Taylor & Francis, Springer, and MDPI, studies were screened against explicit criteria and analyzed thematically. Findings show that teacher performance in literacy learning is a multidimensional construct comprising pedagogical and content knowledge, sustained professional development and coaching, self efficacy beliefs, classroom management and instructional practice, formative assessment literacy, and digital and culturally responsive pedagogy. These dimensions interact synergistically, and their combined presence is consistently associated with stronger student reading and writing outcomes. The review proposes an integrated conceptual framework linking the six dimensions to literacy achievement and offers implications for teacher preparation, in service coaching, and policy in elementary education, including the Indonesian Merdeka Belajar and Minimum Competency Assessment (AKM) context